2016
DOI: 10.3892/mmr.2016.5924
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent endocrine disorders involved in the pathogenesis of refractory acne in women

Abstract: Acne is a disorder of the pilosebaceous unit, common among adolescents, which may be extended to adulthood. The aim of this study was to assess the prevalence of hormonal disorders in women with acne resistance to conventional therapy. We included 72 women aged between 15 and 36 years (divided in two age groups) who presented to our clinic between May and October 2014, suffering from moderate and severe forms of papulopustular and nodulocystic acne. The subjects were non-responsive to classic dermatological tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
23

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 19 publications
0
22
0
23
Order By: Relevance
“…Many patients are colonized at admission with MSSA, located mostly in the pharynx, but also in other sites (3). For example, some of the patients in the present study had acne, from which S. aureus was isolated (27). These MRSA subpopulations can be selected through exposure to cefoxitin or oxacillin up to 48 h (28).…”
Section: Discussionmentioning
confidence: 81%
“…Many patients are colonized at admission with MSSA, located mostly in the pharynx, but also in other sites (3). For example, some of the patients in the present study had acne, from which S. aureus was isolated (27). These MRSA subpopulations can be selected through exposure to cefoxitin or oxacillin up to 48 h (28).…”
Section: Discussionmentioning
confidence: 81%
“…Hence we found that persistent acne is distinctly different from late onset acne and has profound hyperandrogenic features with underlying adrenal and ovarian dysfunction including PCOS. This also suggests that this group, which can manifest as refractory acne, deserves therapy with antiandrogens . AMH and its interrelationship with various androgenic parameters in adult female acne is a potential precept concept that we propose to investigate further to determine its role in adult female acne.…”
Section: Discussionmentioning
confidence: 97%
“…This also suggests that this group, which can manifest as refractory acne, deserves therapy with antiandrogens. 35 AMH and its interrelationship with various androgenic parameters in adult female acne is a potential precept concept that we propose to investigate further to determine its role in adult female acne.…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective properties of secondary metabolites can be attributed, in part, to their antioxidant capacity and anti-inflammatory potential. Genistein, a secondary metabolite of plant origin, has the structure and function similar to the primary female sex hormone, 17-beta-estradiol [84]. Genistein is capable of attaching itself to the receptive proteins of the female sex hormones and having estrogen-specific hormonal effects, even being able to replace them, triggering either an estrogenic or a regulatory hormonal impact [85].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%